The role of structured physiotherapy in treating patients with atraumatic shoulder instability: Medium term results from a case series. (February 2020) - Scott, Martin; Sachinis, Nikolaos Platon; Gooding, Benjamin
Background: Consensus favours conservative treatment for atraumatic shoulder instability, but literature is scarce on the topic. We therefore prospectively assessed the results of structured physiotherapy for these patients. Methods: Patient reported outcomes were recorded prior to physiotherapy and on discharge. Notes review identified patients re-referred for the same condition. Results: N  = 85. Review range was 12–72 months post-treatment. Median Oxford Shoulder Instability Score (OSIS) improved from 21 (range: 2–47) to 39 (11–47). Median Western Ontario Shoulder Instability Index (WOSI) improved from 1117 (range: 306–2028) to 485 (0–1569). Patients with posterior instability demonstrated better results compared with other groups (OSIS change, p  = 0.025; WOSI change, p  = 0.060). Quicker referral to physiotherapy gave improved outcomes (OSIS change, p  = 0.004, rs  = −0.4; WOSI change, p  = 0.047, rs  = 0.24). Twenty-one patients (24.7%) were re-referred, seven of them for repeat physiotherapy and 14 of them for surgery. Previous surgery significantly affected the possibility of a further referral ( p  < 0.001), and initial diagnosis was significantly correlated with further surgery ( p  = 0.032). Discussion: Early referral to physiotherapy may produce better results. Patients with posterior instability responded better to physiotherapy. Previous surgery increased the risk of re-referral. Re-referred patients with posterior instability tended to be managed with further physiotherapy.